IMPLEMENTATION OF THE INTEGRATED NON-COMMUNICABLE DISEASES (POSBINDU PTM) â€œHOPE HEALTHâ€ PROGRAM IN KARANGSALAM VILLAGE, SUSUKAN DISTRICT, BANJARNEGARA REGENCY - Indah Ayu Sofiyanti; Taufik Purboyo; Sartono Sartono (DYNAMICS: Journal of Public Administration, 2023)
This research examines the implementation of the "healthy hope" integrated non-communicable disease development post program (posbindu ptm) in Karangsalam Village, Susukan District, Banjarnegara Regency. The background of this research originated from various problems that occurred at Posbindu Harapan Sehat, especially those related to limited human resources which directly caused various obstacles and other problems. The research method used in this study is a qualitative method with a descriptive approach. Informants in this study were determined by purposive sampling method. While the data analysis in this study was carried out through an interactive analysis model. The results showed that Posbind cadres had sufficient understanding of Posbindu PTM, but the cadres' ability to drive the program was not maximized. The ability to find problems and how to solve them is also not optimal. Then the resources obtained are allocated properly and as needed. The facilities and infrastructure owned are sufficient to realize the program. The authority of various parties such as the Puskesmas, Pemdes, and Village Midwives has run quite optimally in accordance with the 2014 PTM Posbindu Guidelines. Support from various parties such as the Puskesmas, Pemdes, and Village Midwives has also run smoothly and optimally.